Pengaruh Penggunaan Slag Nikel Terhadap Indeks Kekuatan Sisa Campuran HRS-WC - Ferlin Manguma; Alpius; Charles Kamba (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This study was intended to determine the effect of using nickel slag on the residual strength index of the Lataston HRS-WC mixture. The methodology in this research is to carry out a series of coarse and fine aggregate tests then design the composition of the Lataston HRS-WC and HRS-BASE mixture as well as Marshall immersion testing to obtain the Residual Strength Index (IKS) / Immersion Index (IP) / Durability. The results of this study, which was conducted in the Road and Asphalt laboratory of the Faculty of Engineering, Department of Civil, Paulus Makassar, Indonesian Christian University, through the Marshall immersion test, the Lataston HRS-WC mixture was obtained with variations in nickel slag levels of 0%, 25%, 50%, 75%, and 100%. The immersion time duration of 0.5 hours and 24 hours. Marshall test results for Lataston HRS-WC mixture obtained Residual Strength Index (IKS) / Immersion Index (IP) / Durability obtained values ​​of 92.84% for 0% nickel slag content, 93.42% for 25% nickel slag content, 94.19 for 50% nickel slag content, 93.03 for 75% nickel slag content and 97.06% for 100% nickel sag content so that there was an increase in the resistance of the mixture to the residual strength index value in line with the increase in the substituted nickel slag content.